ISOLATION AND ANTIMICROBIAL SUSCEPTIBILITY PATTERN OF MICROORGANISMS CAUSING INTRA-ABDOMINAL INFECTIONS AT TERTIARY CARE HOSPITAL OF NORTHERN INDIA - SINGH, PARMINDER; GARG, RITU; KUMAR, HARIT; RINKU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: The objective of the study is to find out the resistance pattern of pathogenic organisms isolated from intra-abdominal infection (IAI). Methods: A total of 500 samples were collected from suspected IAIs of patients reporting to the hospital and cultured. Identification of the isolates was done using standard identification protocol. Antimicrobial susceptibility was performed by Kirby-Bauer disc diffusion method and interpretation was done using Central Laboratory Standard Institute guidelines. Results: Out of 500 samples, 170 were culture positive and 330 showed no growth. Gram-negative organisms (n=127) outnumbered the Gram-positive organisms (n=23). Among the Gram-negative organisms, Escherichia coli (n=67) was the most commonly isolated bacilli followed by Klebsiella sp. (n=32), Pseudomonas sp. (n=25), Acinetobacter baumannii (n=18), and Klebsiella oxytoca (n=05). Among Gram-positive organisms Staphylococcus aureus (n=17) and Enterococcus spp (n=06) isolates of were grown in culture. Among Gram-negative bacilli, Imipenem followed by Gentamicin was the most effective drug but in Acinetobacter spp. The second most effective drug was Tigecycline. Among Gram-positive isolates, Linezolid was the most effective drug. Conclusion: Prompt starting of empirical antimicrobials based on the local susceptibility pattern, followed by modification of treatment in accordance with the antimicrobial susceptibility report can significantly reduce the morbidity and the mortality associated with IAIs.